2015
DOI: 10.1093/mnras/stv2291
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopy,MOSTphotometry, and interferometry of MWC 314: is it an LBV or an interacting binary?

Abstract: MWC 314 is a bright candidate luminous blue variable that resides in a fairly close binary system, with an orbital period of 60.753±0.003 d. We observed MWC 314 with a combination of optical spectroscopy, broad-band ground-and space-based photometry, as well as with long baseline, near-infrared interferometry. We have revised the singlelined spectroscopic orbit and explored the photometric variability. The orbital light curve displays two minima each orbit that can be partially explained in terms of the tidal … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 64 publications
1
19
0
Order By: Relevance
“…A second model, involving boosting the eccentricity of an orbit during mass transfer, showed the primary mass of MWC 314 was ∼ 14M⊙. The pulsational behavior of MWC 314 that was observed with MOST confirmed the low-mass nature of this system (Richardson et al 2016a). Similar short-period (∼ 6 hr) pulsations were observed in the HD 5980 system by Sterken & Breysacher (1997) after its LBV-like eruption, but the close orbit likely changes the observed stellar structure of these stars compared to other LBV stars.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…A second model, involving boosting the eccentricity of an orbit during mass transfer, showed the primary mass of MWC 314 was ∼ 14M⊙. The pulsational behavior of MWC 314 that was observed with MOST confirmed the low-mass nature of this system (Richardson et al 2016a). Similar short-period (∼ 6 hr) pulsations were observed in the HD 5980 system by Sterken & Breysacher (1997) after its LBV-like eruption, but the close orbit likely changes the observed stellar structure of these stars compared to other LBV stars.…”
Section: Discussionmentioning
confidence: 81%
“…The only similar star that has shown stable pulsations is the LBV candidate MWC 314 (Richardson et al 2016a), which exhibits two pulsations with periods close to 1 d. This star has a spectrum reminiscent of the LBVs like η Carinae, but many of the emission lines are double-peaked, forming in a circumbinary disk. In the case of MWC 314, Richardson et al (2016a) found that the binary was not a massive LBV as previously suggested by Muratorio et al (2008) and Lobel et al (2013), but rather was the evolutionary byproduct of a lower-mass binary interaction. The system was a close spectroscopic twin to the binary HDE 326823 (Richardson et al 2011) where mass transfer has hidden the mass gainer behind a thick accretion torus while leaving the lower mass donor star visible.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An N-body code, box_tree [8,9,28,35,[51][52][53][54], was employed to model the dynamics of the dust system. Particles are trapped within a parabolic potential well in the horizontal direction and by a linear electric field and gravity in the vertical direction (see Eq.…”
Section: Model and Methodsmentioning
confidence: 99%
“…Their components at periastron are separated by only a few stellar radii, giving rise to significant tidal forces that distort stellar surfaces. A total of 28 giants in heartbeat stars have been reported to date (Nicholls & Wood 2012;Gaulme et al 2013Gaulme et al , 2014Beck et al 2014;Richardson et al 2016); of these, there are 9 for which the authors developed a full model (Nicholls & Wood 2012;Beck et al 2014;Richardson et al 2016), all of them under the constant volume…”
Section: Volume Conservation In Eccentric Orbitsmentioning
confidence: 99%